2022
DOI: 10.3390/sym14122497
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spinal Asymmetries on Physical Fitness Parameters in Young Elite Soccer Players

Abstract: The purpose of the study was to examine the effect of spinal asymmetries on specific physical fitness parameters in young elite soccer players. Fifty male soccer players, all members of the under 17 (U17) and 15 (U15) National teams of Cyprus, were initially evaluated for thoracic kyphosis, lumbar lordosis and scoliosis asymmetries. Based on the spinal asymmetries’ initial evaluation, soccer players were categorized into the asymmetry group (AG) and normal group (NG) per spinal asymmetry. Hamstring and lower-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Each CEP was coded with a number and assigned for a condition. Seventeen different programs were designed for thoracic kyphosis (1), lumbar lordosis (2), right thoracic scoliosis (3), left thoracic scoliosis (4), right lumbar scoliosis (5), left lumbar scoliosis (6), anterior pelvic tilt (7), posterior pelvic tilt (8), hamstring stretching (9), hip adductor muscle length-stretching (10), iliopsoas stretching (11), rectus femoris stretching (12), tensor fasciae latae stretching (13), hip external rotator stretching (14), hip internal rotator stretching (15), soleus stretching (16) and gastrocnemius stretching (17) (see Supplementary Materials). In addition, for convenience, the program code was referred to the participants by the researchers during the programs' demonstration.…”
Section: Implementation Of Intervention and Cepsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each CEP was coded with a number and assigned for a condition. Seventeen different programs were designed for thoracic kyphosis (1), lumbar lordosis (2), right thoracic scoliosis (3), left thoracic scoliosis (4), right lumbar scoliosis (5), left lumbar scoliosis (6), anterior pelvic tilt (7), posterior pelvic tilt (8), hamstring stretching (9), hip adductor muscle length-stretching (10), iliopsoas stretching (11), rectus femoris stretching (12), tensor fasciae latae stretching (13), hip external rotator stretching (14), hip internal rotator stretching (15), soleus stretching (16) and gastrocnemius stretching (17) (see Supplementary Materials). In addition, for convenience, the program code was referred to the participants by the researchers during the programs' demonstration.…”
Section: Implementation Of Intervention and Cepsmentioning
confidence: 99%
“…Several studies have previously observed that body posture asymmetry may cause muscle imbalance, musculoskeletal injuries, motor control impairment [1][2][3][4][5][6] and a reduction in exercise performance in young soccer players [7]. Postural asymmetry-induced injuries might be due to early specialization and/or to premature participation in sports [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of hyperkyphosis on lowering the shoulder and indirectly on subacromial impingement syndrome in football players has also been identified [ 28 ]. Another study of athletes in the same sport showed that kyphotic and lordotic posture may negatively affect neuromuscular explosiveness performance, while lateral spine curvature reduces lower limb flexibility [ 29 ].…”
Section: Introductionmentioning
confidence: 99%